Wake-up Sleepy Gene: Reactivating Fetal Globin for β-Hemoglobinopathies. Issue 12 (December 2018) - Wienert, Beeke; Martyn, Gabriella E.; Funnell, Alister P.W.; Quinlan, Kate G.R.; Crossley, Merlin
Abstract : Disorders in hemoglobin (hemoglobinopathies) were the first monogenic diseases to be characterized and remain among the most common and best understood genetic conditions. Moreover, the study of the β-globin locus provides a textbook example of developmental gene regulation. The fetal γ - globin genes ( HBG1/HBG2) are ordinarily silenced around birth, whereupon their expression is replaced by the adult β - globin genes ( HBB primarily and HBD ). Over 50 years ago it was recognized that mutations that cause lifelong persistence of fetal γ‐globin expression ameliorate the debilitating effects of mutations in β - globin . Since then, research has focused on therapeutically reactivating the fetal γ-globin genes. Here, we summarize recent discoveries, focusing on the influence of genome editing technologies, including CRISPR-Cas9, and emerging gene therapy approaches. Highlights: Recent advances in genome editing have enabled a better understanding of globin gene regulation and new therapies for hemoglobinopathies are now within sight. Fetal hemoglobin and its reactivation in adulthood holds great promise for the treatment of hemoglobin disorders, such as sickle cell disease. Our understanding of natural mutations that cause hereditary persistence of fetal hemoglobin (HPFH) has increased. It is now known that small natural deletions and mutations in the fetal globin gene promoters disrupt the binding of the transcriptional repressors BCL11A and ZBTB7A, causing HPFH. Using gene editing to mimic these mutations should reactivate fetal globin in patients with hemoglobin disorders and alleviate the symptoms of hemoglobinopathies.